Peran Pendidikan Jasmani dalam Pembentukan Karakter Siswa di Sekolah Dasar - Rahmat, Ainul; Rais, Risman; Alwi, Alimin; Hudain, Muh Adnan; Usman, Arifuddin (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the role of physical education in shaping the character of primary school students. This study uses a qualitative approach with the Systematic Literature Review (SLR) method on scientific articles published in the last five years (2019–2024). Data were obtained by searching for articles on Google Scholar, ERIC, Scopus, and ResearchGate using the keywords ‘physical education’, ‘character building of students’, ‘primary school’, “TPSR”, and ‘value-based learning’, then selected based on inclusion and exclusion criteria, extracted, and analysed thematically. The findings reveal four key points: (1) physical education significantly contributes to fostering discipline, responsibility, cooperation, sportsmanship, and mutual respect; (2) the main character values developed include discipline, personal and social responsibility, sportsmanship, honesty, cooperation, and empathy; (3) effective learning strategies include TPSR, value-based learning, educational games, and cooperative learning; and (4) implementation challenges involve limited teacher competence, inadequate facilities, restricted instructional time, and insufficient support from schools and parents. The study emphasizes the need for improved teacher competence and adequate learning facilities to optimize the role of physical education in character development